PRESTASI KERJA MEMEDIASI PENGARUH DELEGASI WEWENANG DAN PRODUKTIVITAS KERJA KARYAWAN PT. PLN TANJUNG BALAI - TRI OKTAVIA (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2023)
This research was done in PT. PLN (Persero) Tanjung Balai with the aim of knowing the effected of delegation of authority and work coordination on work productivity with mediation by employee performance. The population were employees who worked in the company as many as 133 people, sampling with census sample so that the number of samples were 133 respondents. Sources of data using primary data and data collection techniques were literature study, observation and questionnaires. Data analysis techniques consist of data quality test, classical assumption test, path analysis and hypothesis testing. Based on the results of the study showed that partially, the delegation of authority had no significant effect on employee work performance and also on employee work productivity, while work coordination had significant effected on employee work performance and employee productivity. Employee work performance has significant effected on employee work productivity at PT. PLN Tanjung Balai. Simultaneously showed that delegation of authority, work coordination and employee performance have positive and significant effected on employees work productivity in PT. PLN (Persero) Tanjung Balai. Work performance mediates the effected of delegation of authority on employees work productivity, but didi not mediate the effected of work coordination on employee work productivity in PT. PLN (Persero) Tanjung Balai. Delegation of authority, work coordination and work performance have moderate correlation to the work productivity of employees at PT. PLN. Work productivity of employees at PT. PLN can be explained by the delegation of authority, work coordination and employee performance of 24.5% and the others 75.5% can be explained by other variables not examined such as training, compensation, incentives and others.